Tau PET following acute TBI: Off-target binding to blood products, tauopathy, or both? - Butler, Tracy; Chiang, Gloria C.; Niogi, Sumit Narayan; Wang, Xiuyuan Hugh; Skudin, Carly; Tanzi, Emily; Wickramasuriya, Nimmi; Spiegel, Jonathan; Maloney, Thomas; Pahlajani, Silky; Zhou, Liangdong; Morim, Simon; et al. (Frontiers in Neuroimaging, 2022)
Repeated mild Traumatic Brain Injury (TBI) is a risk factor for Chronic Traumatic Encephalopathy (CTE), characterized pathologically by neurofibrillary tau deposition in the depths of brain sulci and surrounding blood vessels. The mechanism by which TBI leads to CTE remains unknown but has been posited to relate to axonal shear injury leading to release and possibly deposition of tau at the time of injury. As part of an IRB-approved study designed to learn how processes occurring acutely after TBI may predict later proteinopathy and neurodegeneration, we performed 18F-MK6240 PET and MRI within 14 days of complicated mild TBI in three subjects. PET radiotracer accumulation was apparent in regions of traumatic hemorrhage in all subjects, with prominent intraparenchymal PET signal in one young subject with a history of repeated sports-related concussions. These results are consistent with off-target tracer binding to blood products as well as possible on-target binding to chronically and/or acutely-deposited neurofibrillary tau. Both explanations are highly relevant to applying tau PET to understanding TBI and CTE. Additional study is needed to assess the potential utility of tau PET in understanding how processes occurring acutely after TBI, such as release and deposition of tau and blood from damaged axons and blood vessels, may relate to development CTE years later.